A Unique Au–Ag–Au Triangular Motif in a Trimetallic Halonium Dication: Silver Incorporation in a Gold(I) Catalyst. Issue 37 (9th August 2013) - Zhu, Yuyang; Day, Cynthia S.; Zhang, Lin; Hauser, Katarina J.; Jones, Amanda C.
Abstract As a result of explorations into the solution chemistry of silver/gold mixtures, a unique diphosphine trimetallic chloronium dication was discovered that incorporates silver–arene chelation and a triangular mixed gold/silver core in the solid state. Notably, it was isolated from a Celite prefiltered solution initially thought to be silver‐free. The crystal structure also incorporates the coordination to silver of one fluorine atom of one SbF6− counterion. The structure was compared to two new, but well‐precedented, phosphine digold chloride cations. DFT calculations supported significant silver–halide and silver–arene interactions in the mixed gold/silver complex and metallophilic interactions in all three complexes. Comparison of computed data revealed that the ωB97X‐D functional, which has a long‐range corrected hybrid with atom–atom dispersion corrections, gave a better fit to the experimental data compared with the PBE0 functional, which has previously failed to capture aurophilic interactions. Preliminary studies support the presence of the mixed gold/silver structure in solution.